Countering Democratic Backsliding by EU Member States: Constitutional Pluralism and 'Value' Differentiated Integration. Issue 3 (21st April 2021) - Bellamy, Richard; Kröger, Sandra
Abstract: Constitutional pluralism (CP) and differentiated integration (DI) have been criticised as potentially legitimising democratic backsliding within the EU. Critics contend that effective measures require strengthening the legal authority of the Court of Justice of the European Union and the political authority of the European Commission. We dispute this criticism, which rests on a federal conception of the EU at odds with its confederal features. We argue that the value of democracy for the EU derives from pluralism between as well as within states, thereby justifying CP and DI. While both prove incompatible with democratic backsliding, they challenge the legitimacy of the strong assertions of federal authority some advocate to tackle it. Drawing on CP, we propose four criteria for EU action against backsliding regimes, and suggest processes and penalties that meet them. We liken the latter to 'value' DI, whereby backsliding states can be excluded from EU funding and voting rights. Zusammenfassung: Verfassungspluralismus (VP) und differenzierte Integration (DI) waren in der Vergangenheit dem Vorwurf ausgesetzt, demokratisches Backsliding in der EU zu legitimieren. Kritiker argumentieren, dass effektive Massnahmen die juristische Stärkung des Gerichtshofes der EU und die politischen Stärkung der Europäischen Kommission beinhalten müssen. Wir hinterfragen diese Perspektive, die auf einer föderalen Sicht der EU beruht, aber deren konföderalen Merkmalen zuwiderläuft. Wir argumentieren, dass sich der Wert der Demokratie in der EU aus dem Pluralismus innerhalb sowie zwischen den Mitgliedstaaten ergibt und somit VP und DI rechtfertigt. Beide sind mit demokratischem Backsliding unvereinbar, stellen jedoch die Legitimität starker föderaler Antworten in Frage. Ausgehend von einer verfassungspluralistischen Perspektive entwickeln wir vier Kriterien, denen jegliche EU‐Massnahmen gegen demokratisches Backsliding genügen sollten und schlagen Prozesse und Sanktionen vor, die diesen Kriterien gerecht werden. Wir nennen diese 'wertebezogene' DI, und verbinden damit den Stop der Ausschüttung von EU‐Mitteln sowie die Aberkennung von Stimmrechten im Rat. Résumé: Le pluralisme constitutionnel et l'intégration différenciée ont été accusés de légitimer le recul démocratique au sein de l'Union Européenne (UE). Certains critiques soutiennent qu'il faut renforcer l'autorité de la Cour de Justice de l'UE et de la Commission Européenne. Nous contestons cette critique qui s'appuie sur une conception fédérale de l'UE en décalage avec ses traits confédéraux. Nous considérons que la démocratie en Europe est fondée sur un double pluralisme, celui au sein des états‐membres et celui entre les états‐membres, qui justifie le pluralisme constitutionnel et l'intégration différenciée. Ces derniers sont incompatibles avec le recul démocratique, mais ils mettent aussi en question la légitimité de certaines revendications d'autorité fédérale proposées pour y faire face. Nous proposons quatre critères auxquels l'action de l'UE en réponse à ces reculs démocratiques doit se conformer et recommandons des processus et des sanctions en adéquation avec ces critères. Ces derniers outils permettent de bloquer l'accès aux financements européens des états‐membres incriminés, et de limiter leurs droits de vote au sein du Conseil de l'UE.